EXPRESSION OF THE NEEDS OF THE CHARACTERS OF FAIRY TALES CREATED BY CHILDREN GROWING UP IN FAMILIES AT SOCIAL RISK AND THEIR SATISFACTION - Braziene, Nijole (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The scientific literature analyses in detail the problems of a family at social risk, threats to the child’s social and personality development, etc., however, all insights are provided from an adult perspective – research that would allow the voice of a child growing up in a family at social risk to be heard has not been detected. Children have a limited ability to talk about their experiences. This is facilitated by the creation of a fairy tale, where the child, through the images of the characters created, can safely convey his/her individual life experiences. The aim of the article is to identify the expression of the needs of the characters of fairy tales created by children growing up in families at social risk and their satisfaction. Fairy tales created by 9‒12 year old children were selected as the object of analysis. Of the 69 texts written by children, 47 were selected for analysis. The content analysis of fairy tales was based on the principles of phenomenological hermeneutics. The analysis of fairy tales created by children growing up in families at social risk shows that the characters of the fairy tales they create experience the following unmet needs: physiological, security and social. Heroes of the fairy tales of children growing up in families at social risk are not prone to solving problems, it is more comfortable for them to live as usual, although not always they feel good because of that.